The Murder of Roger Ackroyd - Christie, Agatha, 1890-1976.; Lachard, Bruno (London : Harper, 2007)
Inspector Hercule Poirot, having retired to the small English Village of King's Abbot, is drawn into the investigation of the murders of the widow Mrs. farrars and her suitor, local squire Roger Ackyord.
Comic book edition.
Keywords: Comic books and cartoons; Mystery fiction; Private investigators -- England -- Fiction